TRANSFORMER SYMPATHETIC INRUSH CURRENT IDENTIFICATION CRITERION BASED ON THE VARIATION CHARACTERISTICS OF NON-PERIODIC COMPONENTS - Li, Zhendong; Jin, Haiwang; Sun, Chuanyu; Li, Jinbo; Duan, Shuangming (Scientific Bulletin. Series C, Electrical Engineering and Computer Science, 2025)
The protection will be disactivated because the second harmonic content of the differential current is less than the fixed value following the temporary saturation of the current transformer (CT) caused by the non-periodic component of the transformer sympathetic inrush current. However, when the transformer has turn-toturn faults, the second harmonic content of the differential current is higher than the customized one, resulting in differential protection refusal. These issues are used to analyze the transformer differential protection misoperation behavior, study the mechanism of the transformer sympathetic inrush current and how it differs from fault current, and identify the slow change of the non-periodic component when sympathetic inrush current occurs in the transformer. Furthermore, to prevent maloperation when the CT is saturated, an identification criterion based on variations in the aperiodic component has been incorporated. As an addition to the conventional differential protection, a complete set of identification methods for sympathetic inrush current based on the change of nonperiodic components is further constructed. PSCAD/EMTDC simulation is used to confirm the suggested method's efficacy.